PENANAMAN NILAI KEWIRAUSAHAAN YANG ALKITABIAH KEPADA MASYARAKAT DUSUN BONENGGAYA DENGAN MEMBERDAYAKAN BAHAN BAKU JAHE - Lasmaria Rohani Pakpahan; Yulius Karipi Tanandima; Hempri Apriliyanto Salawaney; Raymon Imanuel Biaf (Jurnal PKM Setiadharma, 2021)
Dusun Bonenggaya is one of the places in Pakava Village, Riopakava District, Donggala Regency, Central Sulawesi Province which has great opportunities in improving the economy, but lack of knowledge so that local people do not know how to manage their natural products. increased so that it greatly affects poverty. The importance of the role of God's servants to provide insight for the community is not only to improve life in spirituality but to balance it with physical needs for the welfare of people's lives. Empowering the community in making instant ginger is one of the services carried out in the field to increase the level of the economy. Thus, this paper answers how to instill the values ​​of entrepreneurship that are biblical or in accordance with God's word.